The mechanisms of nature-based therapy on depression, anxiety, stress, and life satisfaction: examining mindfulness in a two-wave mediation model - Kang, Minjung; Yang, Yeji; Kim, Hyunjin; Jung, Songhie; Jin, Hye-Young; Choi, Kee-Hong (Frontiers in Psychology, 2023)
Background: Nature-based therapy (NBT), which centers around engaging in activities within natural surroundings, has consistently demonstrated therapeutic benefits for mental health. While NBT highlights the potential of nature as a therapeutic resource for promoting mental health, there is limited knowledge regarding its underlying mechanisms. Methods: Two hundred seventy-six Korean participants (204 women, mean age = 54.99 ± 23.25 years) participated in a 30-session gardening program held twice weekly for 15 weeks. Structural equation modeling with a two-wave autoregressive cross-lagged model was used to investigate the mediating effects of mindfulness. Results: NBT significantly improved the mean scores of all psychological variables. The mediation model was partially confirmed, with mindfulness at post-intervention (T2) mediating the relationship between baseline (T1) depression and anxiety and post-intervention (T2) life satisfaction. However, no significant indirect effect was observed between the path from stress (T1) to life satisfaction (T2). Conclusion: Mindfulness is a crucial component for improving mental health outcomes. This study underscores the need to prioritize and emphasize mindfulness practices in NBT.